Kampus Merdeka Sebagai Wadah Pengembangan Metode Mengajar Yang Kreatif Melalui Pendekatan Kampus Mengajar Untuk Memperkuat Literasi Numerasi Dan Teknologi Di Smp Al-Huda Surabaya - Marta Uli Septiana Manalu; Cholis Hidayati (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Independent Learning-Independent Campus is a policy of the Minister of Education and Culture which encourages students to study various fields in order to enter the world of work. The Independent Learning-Campus Independent Policy is guided by Permendikbud Number 3 of 2020 concerning Higher Education National Standards. Students as "agents of change" in developing human resources by contributing and improving together to benefit society. Students in this program go through many processes including registration, selection, debriefing, assignment, and student withdrawal. The Merdeka Learning-Independence Campus Program (MBKM) is a concept-based Merdeka-Learning program that allows students to develop and contribute, especially on issues related to education. The Teaching Campus contributes to the world of education at the elementary (SD) and junior high (SMP) levels in the 4T region (Foremost, Outermost, Disadvantaged, and Transmigration Zones), as well as schools accredited under A. This study aims to determine the role of campus students teaching in helping improve literacy, numeracy at AL-HUDA Middle School, Surabaya, East Java in order to improve the quality of education in Indonesia. Techniques and instruments used in data collection, such as interviews, observation, and documentation. Based on the results of this study, it can be interpreted that campus teaching students play an important role in increasing literacy, numeracy, and technology adaptation in schools